2022
DOI: 10.3389/fphar.2021.817874
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin Reduces Oxidative Stress and Apoptosis in Ventilator-Induced Lung Injury via JAK2/STAT3

Abstract: Mechanical ventilation is an effective treatment for acute respiratory distress syndrome (ARDS), which can improve the prognosis of ARDS to a certain extent. However, it may further aggravate lung tissue injury, which is defined as ventilator-induced lung injury (VILI). Intermedin (IMD) belongs to the calcitonin gene-related peptide (CPRP) superfamily. Our previous studies have found that IMD reduces the expression proinflammatory cytokines, down-regulates nuclear translocation and improves the integrity of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…ROS can modulate a number of cell signaling pathways, including the JAK2–STAT3 pathway ( 19 , 20 ). STAT3 is a transcription factor, which serves a pivotal role in tumor cell proliferation and progression ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…ROS can modulate a number of cell signaling pathways, including the JAK2–STAT3 pathway ( 19 , 20 ). STAT3 is a transcription factor, which serves a pivotal role in tumor cell proliferation and progression ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, VILI is also considered as a biological injury [2,23]. Relevant studies have shown that JAK2-STAT3, PI3/Akt, NF-κB, p38/MAPK, and other signaling pathways can mediate inflammation and/or apoptosis and act on VILI progression [20,[24][25][26][27]. However, it is still necessary to explore the key points in the pathogenesis network of VILI.…”
Section: Discussionmentioning
confidence: 99%
“…DMSO as placebo and SB216763 as GSK-3β inhibitor (MedChemExpress, Shanghai, China). They were transfected into cells by Lipofectamine 3000 reagent (Thermo Fisher Scientific, U.S.A.) before cyclic stretching with Flexcell Tension PluFX-4000TM (Flexcell International Corporation, Burlington, U.S.A.) [20].…”
Section: Cell Experimentsmentioning
confidence: 99%
“…Apoptosis of lung cells plays a pivotal role in ALI/ARDS development [ 55 , 56 ]. Therefore, it is urgent to solve the problem of apoptosis in ALI/ARDS.…”
Section: Discussionmentioning
confidence: 99%